2005
DOI: 10.1007/s00204-004-0643-3
|View full text |Cite
|
Sign up to set email alerts
|

L-Carnitine halts apoptosis and myelosuppression induced by carboplatin in rat bone marrow cell cultures (BMC)

Abstract: Carboplatin (CP), a second generation platinum compound, is effective against various types of cancers, producing less nephrotoxicity and ototoxicity but more myelotoxicity than cisplatinum. CP-myelosuppression is the rate-limiting step of its clinical use. Prevention of CP-myelosuppression is a major target in the field of chemotherapy. Therefore, the present study investigates the use of L-carnitine (LCR)-an antioxidant, cardioprotective, neuroprotective, and immunostimulant nontoxic natural compound-to prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 38 publications
4
22
0
Order By: Relevance
“…This may not only enhance antitumour activity of carboplatin, but it may also increase haematological toxicity. This hypothesis is supported by the effect of L-carnitine, which protects against carboplatin-induced myelosuppression by increasing the intracellular glutathione content during treatment with carboplatin (Abd-Allah et al, 2005).…”
Section: Discussionmentioning
confidence: 86%
“…This may not only enhance antitumour activity of carboplatin, but it may also increase haematological toxicity. This hypothesis is supported by the effect of L-carnitine, which protects against carboplatin-induced myelosuppression by increasing the intracellular glutathione content during treatment with carboplatin (Abd-Allah et al, 2005).…”
Section: Discussionmentioning
confidence: 86%
“…On the other hand, numerous in vitro experiments have demonstrated that carnitine and its derivatives acetylcarnitine (Fig. 3B) and propionylcarnitine have anti-apoptotic properties [78][79][80], most likely by preventing SM breakdown and consequent Cer synthesis; this effect seems to be specific for aSMase [reviewed in 81].…”
Section: (A) Acidic Sphingomyelinase Inhibitorsmentioning
confidence: 99%
“…However, besides this well-known effect, there is growing evidence that L-carnitine also plays a role in other physiological processes in humans and animals. Indeed, L-carnitine and some of its acyl esters act as very potent reactive oxygen species scavengers25,26 and are known to have immunomodulatory properties in mammalian as well as avian species 27. Although recent studies have attended to the role of L-carnitine in treatment of male infertility during sepsis, the exact mode of action still needs to be explored.…”
Section: Introductionmentioning
confidence: 99%